MENGGALI MAKNA TRADISI PASSOMPE’ DALAM WARISAN BUDAYA MARITIM INDONESIA - Putra, Attila Fath Haeril; Darwis, Darwis; Nugraha, Imam Fadhil (Cahaya Ilmu Bangsa, 2024)
This research explores the meaning and role of the passompe' tradition in Bugis society as part of Indonesia's maritime cultural heritage. Passompe', which refers to the overseas and seafaring activities of the Bugis, had a significant impact not only in economic terms, but also in strengthening the cultural and social identity of the Bugis people. Using descriptive analysis and literature review methods, this article analyses the contribution of passompe' in shaping the Bugis diaspora, its influence on cross-border trade, and the social values of courage, solidarity and adaptability passed on. It shows how Bugis-Makassar maritime culture enriches Indonesia's cultural heritage and strengthens its position as a maritime nation. Penelitian ini menggali makna dan peran tradisi passompe’ dalam masyarakat Bugis sebagai bagian dari warisan budaya maritim Indonesia. Passompe’, yang merujuk pada kegiatan perantauan dan pelayaran suku Bugis, memiliki dampak yang signifikan tidak hanya dalam aspek ekonomi, tetapi juga dalam memperkuat identitas budaya dan sosial masyarakat Bugis. Dengan metode analisis deskriptif dan kajian pustaka, artikel ini menganalisis kontribusi passompe’ dalam membentuk diaspora Bugis, pengaruhnya dalam perdagangan lintas wilayah, serta nilai-nilai sosial seperti keberanian, solidaritas, dan adaptabilitas yang diwariskannya. Tradisi ini menunjukkan bagaimana budaya maritim Bugis-Makassar memperkaya warisan budaya Indonesia dan memperkuat posisi sebagai negara maritim.